ESTIMATION OF BIOMASS AND CARBON CONTENT IN EX-COAL MINE LANDS - Wirawan Noor Hadi; Gusti Muhammad Hatta; Yudi Firmanul Arifin; Fakhrur Razie (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2016)
Potentially acid forming (PAF) and non-acid forming (NAF) lands are two types of lands found in ex-coal mine lands. These lands are similar to wetlands that have the potential to produce acid. PT. Jorong Barutama Greston is one of the coal mining companies required by the government to carry out reclamation by revegetation activities. Revegetation of ex-coal mine lands has generated plant biomass and carbon content to a specific value. The purposes of this study were to compare the amount of biomass and carbon content in ex-coal mine lands and to determine the best treatment for the ex-coal mine lands. The methods began with creating the measuring plots on the lands with different soil color (gray and brown). The soil color difference was determined by laboratory analysis test. For each different soil, the land revegetation was implemented with different treatments, 4 ameliorant treatments and 2 fertilization treatments so there were 8 units of treatments. Biomass and carbon content in each treatment unit were calculated by taking 4 plants as the laboratory test samples. The carbon content was calculated using the formula calculating the carbon of undergrowth with a diameter of < 5 cm. The results showed that the biomass and carbon content of plants in plot II were 17 times higher than those in plot I. The best treatment in plot I was the use of lime, bokashi and LOF (Liquid Organic Fertilizer) while the best treatment in plot II was the use of bokashi.